The health impact of hazardous waste landfills and illegal dumps contaminated sites: An epidemiological study at ecological level in Italian Region - Fazzo, Lucia; Manno, Valerio; Iavarone, Ivano; Minelli, Giada; De Santis, Marco; Beccaloni, Eleonora; Scaini, Federica; Miotto, Edoardo; Airoma, Domenico; Comba, Pietro (Frontiers in Public Health, 2023)
Background and aim. The implementation of idoneous management of hazardous waste, including the contrast to illegal practices, is among the Environment and Health priorities of WHO. The aim of the present study, based on a collaborative agreement between the Italian National Health Institute and a Prosecution Office located in Naples North, was to evaluate the health effects of illegal landfills and burning of urban and hazardous waste, in the territory of the Prosecution Office. Methods. The municipalities included in the study territory were investigated, with respect to the regional population. Regression analyses were performed into the study area between 4 classes of an environmental municipal indicator of waste risk (MRI) previously defined, computing the Relative Risks (RRs) in 2-4 MRI classes, with respect to the first MRI class (the least impacted). The prevalence of reproductive outcomes and cause-specific mortality and hospitalization were analyzed, in general population and 0-19 age class, using SAS software Results. Excesses of mortality and hospitalization in both genders of the whole area, with respect to regional population, were found for: overall cancers and cancer of stomach, liver, lung and kidney, and ischemic heart diseases. Excesses of mortality for leukemias in 0-19 old population and of hospitalization for certain conditions originating in the perinatal period were observed. A correlation with MRI was found in the risk of mortality from breast tumours in women (MRI class 2: RR=1.06; MRI class 3: RR=1.15; MRI class 4: RR=1.11) and hospitalization from testis tumours (MRI class 2: RR=1.25; MRI class3: RR=1.31; MRI class 4: RR=1.32). The hospitalization from breast tumours and asthma exceeded significantly in both genders of 3 and 4 MRI classes. Among 0-19 years people, a correlation with MRI was found in hospitalization from leukemias (MRI class 2: RR=1.48; MRI 3 class: RR=1.60; MRI class 4: RR=1.41) and in prevalence of preterm birth (MRI class 2: RR=1.17; MRI class3: RR=1.08; MRI class4: RR=1.25). Conclusions. A correlation between health outcomes and the environmental pressure by uncontrolled waste sites was found. Notwithstanding the limitation of the study, the results push to implement actions of evironmental remediation and prosecution of illegal practices.